Between Discourses of Extreme Pressure and Modernization: Small Farmers’ Diverse Perceptions of Vulnerability to Soy in Santarém, Pará - Theis, Sophie; Swette, Briana (Consilience, 2012)
The socio-ecological implications of the soybean agricultural expansion in the Brazilian Amazon cannot be fully understood without examining the interactions between soy and small farmers. The expansion of soy in Santarém following the construction of the Cargill port in 2001 has affected local smallholders, but how and to what degree is the subject of significant controversy. Discourse has emerged describing the impact of soybean agricultural expansion on the small farmers of the region. One discourse, which we term the modernization discourse, depicts effects on smallholders like migration as natural and welfare-improving. In opposition, a second discourse, which we term the extreme pressure discourse, portrays smallholders as struggling to survive under social, economic, and biological pressures associated with rapid land-use change due to soy. However, characterizing smallholders’ livelihoods as vulnerable too often assumes that smallholders have a single, homogenous experience of the expansion of soy agriculture and that they are unable to adapt to changes. Interviews with smallholders who remain farming in 20 communities of rural Santarém reveal heterogeneity in farmers’ perceptions to the soybean-smallholder conflict. Understanding of vulnerability must expand to encapsulate farmers’ adaptive capacity. Smallholders do express a desire and capacity to maintain a rural livelihood and their farming identity amidst the land-use change. Smallholders’ perceptions of the impacts of the soy frontier complicate both extremes of public discourse vis-à-vis the soy conflict.